Impacts of community-based rehabilitation program (centre-based care vs. home-based care) on health outcomes among children with disabilities in east coast region of Peninsular Malaysia - Hasan, Haliza; Abdul Aziz, Aznida Firzah; Mohd Nordin, Nor Azlin; Aljunid, Syed Mohamed (2023)
Objective: Community-based rehabilitation (CBR) is one of the realistic and necessary programs to assist vast numbers of people with disabilities including children to improve their health outcomes and quality of life. Thus, this study aimed to determine the impacts of CBR program on health outcomes of children participated in CBR programme. Methods: The cross-sectional study design was conducted in three states in east coast region of peninsular Malaysia and employed two sampling methods which were multi-staged sampling method and universal sampling method. A total of 297 children registered with the Department of Social Welfare as CBR trainee during the period of study were recruited. The Barthel Index of Activities of Daily Living, Developmental Disability–Children Global Assessment Scale, and Health Related Quality of Life were used to assess the health outcomes of children with disability participated in CBR programmes. The health outcomes were compared for current score during data collection with previous 6 months, and children who changed type of programme within data collection period were excluded. Results: The result showed that children in centre-based care had significantly more favorable developmental disability, quality of life, and quality adjusted life years compared to home-based programme, where p < 0.001 respectively. Conclusions: Centre-based care has better impact on health outcomes compared to the home-based care. However, this study observed the effects only a one-time score which might have underestimated the ongoing benefit in terms of health outcomes.